Association of Histopathological Parameters and Axillary Lymphnode Metastasis in Primary Breast Carcinoma - purushotham, Manjula K; Venkatesh, Pradeep Mitra (Asian Pacific Journal of Cancer Care, 2021)
Introduction: The most common malignancy worldwide among females is breast carcinoma and the second most common malignancy in India, next to cervical cancer. A wide range of potential prognostic features have been studied in breast cancer and are mainly divided into two groups i.e. Histopathological and Molecular. The histological features are cost-effective and provide reliable diagnostic and prognostic information in these tumors. Axillary Lymph node status is one of the most important prognostic factors and greatly affects the morbidity and mortality of the patient. Materials and Methods: All breast cancer specimens received in the Department of Pathology over a period of five years. The following histopathological parameters were carefully studied like Tumor size, Histological type, Grade, Presence of necrosis, Inflammatory cell infiltrate, Lymphatic invasion, Blood vessel invasion, Perineural invasion, and other Stromal changes were studied in detail, and association of these histopathological parameters with axillary lymph node metastasis were analyzed. Results: A total of 100 cases were studied, and most of the patients were over the age of 50. The maximum number of cases was in the T2 stage (55%). Infiltrating ductal carcinoma (88%) was the most common type of tumor encountered in the study. The majority of the cases were Grade I tumors. Skin Invasion was seen in 14% and Lymphovascular Invasion was seen in 17% of cases respectively. There was a statistically significant association between the size of the tumor, T stage, Grade of the tumor, necrosis, and inflammatory infiltrate on further analysis. Conclusion: There was a statistically significant correlation between Tumor size, pathological T stage, Grade of the tumor, Necrosis and inflammatory infiltrate with axillary Lymph node metastasis in the present study. Increased tumor size, T stage, higher grade, presence of necrosis and low inflammatory infiltrate are associated with increased axillary Lymph node metastasis.